2017
DOI: 10.1371/journal.pone.0170710
|View full text |Cite
|
Sign up to set email alerts
|

A Special Tear Pattern of Anterior Horn of the Lateral Meniscus: Macerated Tear

Abstract: BackgroundWe describe a special, interesting phenomenon found in the anterior horn of the lateral meniscus (AHLM): most tear patterns in the AHLM are distinctive, with loose fibers in injured region and circumferential fiber bundles were separated. We name it as macerated tear. The goal of this study was to bring forward a new type of meniscal tear in the AHLM and investigate its clinical value.Materials and MethodsAHLM tears underwent arthroscopic surgery from January 2012 to December 2014 were included. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Anterior horn meniscal injury is a rare entity and only three case series with small samples have been previously published, focusing on lateral meniscus [ 8 , 18 , 22 ]. Choi et al used all-inside technique in seven young male footballers, with return to sport at six months after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Anterior horn meniscal injury is a rare entity and only three case series with small samples have been previously published, focusing on lateral meniscus [ 8 , 18 , 22 ]. Choi et al used all-inside technique in seven young male footballers, with return to sport at six months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Hagino et al reported great improvement in mean Lysholm score 12 months postoperatively, similar to our results in 8 young male footballers with anterior horn tears of the lateral meniscus, although treatment modality was not consistent (only two tears were repaired, the rest were partially excised) [ 8 ]. In the study by Zhen et al which focused on anterior horn tears of the lateral meniscus, patients with anterior horn tears were organized based on tear morphology [ 18 ]. The macerated tear type was present in the majority of patients (42%), the other three being horizontal tears, vertical tears or complex tears.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the flexion angle is less than 30°, the anterior medial meniscus horn withstands a high shear strength and prevents the femur from antedisplacement [9,10]. PCL can prevent retrodisplacement of the tibia [11], meanwhile, the anterior medial meniscus horn can prevent antedisplacement of the femur [12], the two coordinately prevent the excessive motion of the knee joint. In our case, however, the PCL couldn't bear the tension caused by the excessive motion of the knee joint, and thus a high shear was exerted to the anterior medial meniscus horn, leading to traumatic avulsion of the AMMR complicated with PCL injury.…”
Section: Discussionmentioning
confidence: 99%